1982
DOI: 10.1177/0011000082102008
|View full text |Cite
|
Sign up to set email alerts
|

Position Paper: Cross-Cultural Counseling Competencies

Abstract: An exploration of experiences, preferences and predictors of satisfaction in clinical supervision with play therapists. (Unpublished doctoral dissertation).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
820
0
9

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 854 publications
(850 citation statements)
references
References 19 publications
8
820
0
9
Order By: Relevance
“…In terms of multicultural counseling practice, various models have been developed (see Fuertes & Gretchen, 2001;Ponterotto, Fuertes, & Chen, 2000 for reviews). Although its empirical foundation has been questioned, the multicultural counseling competency model, proposed and revised by Sue and his colleagues (Sue et al, 1992;Sue et al, 1982), has been extensively adopted by counseling training programs.…”
Section: Guidelines For Cultural Competence In the Treatment Of Ethnimentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of multicultural counseling practice, various models have been developed (see Fuertes & Gretchen, 2001;Ponterotto, Fuertes, & Chen, 2000 for reviews). Although its empirical foundation has been questioned, the multicultural counseling competency model, proposed and revised by Sue and his colleagues (Sue et al, 1992;Sue et al, 1982), has been extensively adopted by counseling training programs.…”
Section: Guidelines For Cultural Competence In the Treatment Of Ethnimentioning
confidence: 99%
“…Bandura (1997) (Constantine & Ladany, 2001;Sue, 2001;Sue et al, 1982;Sue et al, 1992); (b) models of multicultural counseling (D'Andrea & Daniels, 2001;Fuertes & Gretchen, 2001;Ponterotto et al, 2000); (c) assessment of multicultural counseling competence (Coleman, 1996;D'Andrea et al, 1991;LaFromboise et al, 1991;Ponterotto et al, 2002;Sodowsky et al, 1994;Worthington, Mobley, Franks, & Tan, 2000); and (d) training of multicultural competencies (Abreu et al, 2000;Constantine, 2001a;Constantine & Ladany, 2000;Constantine, Ladany, Inman, & Ponterotto, 1996;Ponterotto & Casas, 1987;Quintana & Bernal, 1995). In addition to the progress made in theory and assessment, a recent survey indicated that 73% of APA-accredited counseling psychology programs offered one or more multicultural courses, and 42% of them required a multicultural course (Quintana & Bernal, 1995).…”
Section: General Cse Measures: Why They Are Not Sufficient For Multicmentioning
confidence: 99%
“…Even though multicultural competencies have most commonly been defined as a culmination of awareness, knowledge, and skills (Dunn, Smith, & Montoya, 2006;HolcombMcCoy & Day-Vines, 2004;Kocarek et al, 2001;Penderson, 1991, Pope-Davis & Dings, 1994Pope-Davis & Dings, 1995;Ridley & Kleiner, 2003;Sue, Arredondo, & McDavis, 1992;Sue, Bernier, Durran, Feinberg, Pendersen, Smith, et al, 1982), there is a significant need to consider alternative concepts that may contribute to a counselor's multicultural proficiency (Kitaoka, 2005). When viewed as a composite palate from which to draw, the MCCTS-R, MCI, MCAS-B, MAKSS, and CCCI-R can all provide valuable resources to reference when building an instrument specifically to assess practicing school counselors' MCCs.…”
Section: Creation Of the Initial Instrument Purposementioning
confidence: 99%
“…Broadly defined, psychology students must achieve multicultural competence on three dimensions: awareness, knowledge, and skills (Sue, Arredondo, & McDavis, 1992;Sue et al, 1982). Awareness of salient multicultural factors such as age, gender, race, ethnicity, physical ability, sexual orientation, religion and socioeconomic status, may be one of the earliest steps in moving towards cultural competence (APA, 2002).…”
Section: Introductionmentioning
confidence: 99%